(untitled) (Research, Society and Development, 2023)
Insect meal is considered an alternative source of several nutrients, gaining prominence mainly for its high protein content and high fat content. In addition to its nutritional benefits, several studies show that its use can be considered a more sustainable and technically feasible solution, thus proving to be a promising substitute for commonly used protein ingredients. The present review aimed to describe the most recent results on the use of insects in laying hen feed. A compilation of papers on the use of insect meal in laying hen feed on production, health, and performance indices was performed using the Scielo, Google Scholar, and Portal Capes research platforms. We conclude that it is possible to gradually replace the protein ingredient by insect meal in diets in laying hens, enabling improvement in egg quality and quantity.